(Re) construyendo el pasado y el presente: Un debate sobre las posibilidades analíticas y metodológicas para la reflexión sobre la sexualidad masculina en el norte del Perú - Álvarez Chávez, Roland (2020)
This paper constitutes an attempt to analyze the localized practices of male sexuality, extrapolating two spaces in particular, the Moche temples on one side, and the chicheríos of the northern coast on another. The research will identify certain elements of analysis, which would configure an epistemological proposal that would allow me to identify certain permanencies and transformations operated in the interactions between the male subject and his otherness. In addition, the article proposes a reflection on self-ethnography as a method of approaching the social reality, based on experience and embodied / located knowledge. Moreover, it is important to mention that this paper is a first approximation, which is a work that has been advancing step by step, first finding and analyzing archaeological / material and historiographic evidence, and then introducing the sociological and anthropological categories and approaches. I know that the article still has issues to develop and deepen further, which I try to systematize in the conclusions as potential issues to continue.